Implementation of Learning to Read Writing The Quran (BTQ) Qutab System and Their Relevance in Early Children's Education - Nurul Hikmah (Edukasi Islami: Jurnal Pendidikan Islam, 2022)
Qutab is an informal institution that is equivalent to primary education (SD) or Islamic Elementary School (MI) using the curriculum of Faith before the Qur'an and Adab before science that applies learning to read and write the Koran through the system Qutab, but many of the people who do not understand about Islamic education institution that has existed since the time of Muhammad. Qutab, where the system can bring great generations.The purpose of this study was to describe: 1) Implementation of learning to read and write the Koran system Qutab in Qutab; 2) Relevance for young children; 3) supporting factors; 4) factors inhibiting the implementation of learning to read and write Quranic system Qutab, and 5) The solution of the inhibiting factors. The methods used in achieving the objectives of this research use qualitative methods pitch. The results obtained from this study showed that: a) the implementation process of learning to read and write the Qur'an (BTQ) Qutab system in     Qutab is done in several stages starting from the first opening that includes welcoming the students in front of the page Qutab, apple pledge students. The second stage consists of the planter’s core concepts, practice, and skill. The third and final phase of closure includes an evaluation and closing greetings; b) the relevance of learning to read and write the Quran for young children is significant once in the presence of this study because it will help in the understanding of the Koran; c) supporting factors: motivation, family, teachers, facilities, amenities, and focus; d) the inhibiting factors: students' thinking, behavior, environment, media, facilities, teachers, parents; and e) Solution of obstacles: Adab before science, communication with parents, counseling, monthly tahsin study.